KARAKTERISTIK ALIRAN MINYAK-AIR DENGAN RASIO VISKOSITAS RENDAH DI PIPA HORIZONTAL DENGAN CFD - Eli Kumolosari; Teguh Wibowo; Ndaru Atmi Purnami (Scientific Journal of Mechanical Engineering Kinematika, 2024)
Two-phase flow is crucial in various fields, particularly in the oil industry, where oil-water flows are common in offshore production wells. Oil is transported with water during its process, and Core Annular Flow (CAF) is one flow pattern that enhances transportation efficiency. This study uses CFD simulations to analyze oil-water flow with a low viscosity ratio in a horizontal pipe (L/d = 30). The aim is to determine the superficial velocities of oil and water (Jo and Jw) that form CAF flow patterns and calculate pressure drop and water hold up. Validation was conducted using experimental data for accuracy. Results show three flow patterns: stratified flow, CAF, and wavy flow. Pressure drop increases linearly with rising J values, from 0.0414 kPa at Jo = 0.21 m/s to 0.6898 kPa at J2 = 2 m/s. The relationship between pressure drop and water hold up is nonspecific, likely due to shear stress in two-phase flow. Pressure drop in the CAF pattern is lower than in stratified flow at the same J values, aligning with theoretical predictions.